The Effect of Reward System and Achievement Motivation on Work Satisfaction of High School Teachers In Region 3 OKU Selatan - Marlina, Winda; Lian, Bukman; Putra, Muhammad Juliansyah (Yayasan Sembilan Pemuda Indonesia, 2023)
The reward system is something that is of concern to everyone, considering that appreciation means giving something related to work performance. A good reward system can also be part of a person’s motivation to excel. For this reason, this study examines the reward system and achievement motivation on job satisfaction felt by teachers. To conduct research in accordance with these rules, the researcher refers to research with quantitative methods. The data obtained through questionnaires and documentation. Data analysis was carried out through simple and multiple linear regression tests, because the data obtained was normally distributed and met the test requirements. The results of the research conducted state that the reward system partially has a significant influence on the job satisfaction of high school teachers in South OKU Rayon 3, as well as achievement motivation which is partially proven to contribute to teacher job satisfaction. The simultaneous testing stated that the reward system and achievement motivation were proven to have a significant influence on the job satisfaction of high school teachers in Rayon 3 OKU Selatan.